The Role of Job Satisfaction and Organizational Citizenship Behavior on Performance: Evidence from Indonesian Teachers - Budi Santoso, Priyono; Asbari, Masduki; Siswanto, Edy; Fahmi, Khaerul (IJOSMAS, 2020)
This study aimed to measure the effect of job satisfaction and organizational citizenship behavior on the teacher performance of private school teachers in Tangerang. The data collection was done by simple random sampling via electronic to the private school teacher population in Tangerang. The returned and valid questionnaire results were 113 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that job satisfaction and organizational citizenship behavior have a positive and significant effect on teacher performance. Besides, job satisfaction has a positive and significant effect on organizational citizenship behavior. This new research proposed a model for building the teacher performance among the private school teachers in Tangerang through enhancing job satisfaction and organizational citizenship behavior. This research could pave the way to improve teacher readiness in facing the era of education 4.0.